2019
DOI: 10.3168/jds.2018-16035
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effects of changing teatcup removal and vacuum settings on milking efficiency of an automatic milking system

Abstract: The aim of this experiment was to assess strategies to reduce milking time in a pasture-based automatic milking system (AMS). Milking time is an important factor in automatic milking because any reductions in box time can facilitate more milkings per day and hence higher production levels per AMS. This study evaluated 2 end-of-milking criteria treatments (teatcup removal at 30% and 50% of average milk flowrate at the quarter-level), 2 milking system vacuum treatments (static and dynamic, where the milking syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…However, Silva Boloña et al (2020) reported a 30-s reduction in MD Q by increasing the milk flowrate switch-point from 30 to 50% of the quarter rolling AMF for the SQ, but this reduction was in quarter MD rather than udder MD, as reported in the present study. The small differences in milk flowrate at teatcup removal between both treatments appeared to be the main factor affecting the lack of differences on MD, in agreement with data reported by Upton et al (2019) and Silva Boloña et al (2019). The 50% milk flowrate switch-point is the maximum that can be set by the user in this AMS, and it is possible that a higher switch-point might produce a significant effect on MD.…”
Section: Short Communicationsupporting
confidence: 90%
See 2 more Smart Citations
“…However, Silva Boloña et al (2020) reported a 30-s reduction in MD Q by increasing the milk flowrate switch-point from 30 to 50% of the quarter rolling AMF for the SQ, but this reduction was in quarter MD rather than udder MD, as reported in the present study. The small differences in milk flowrate at teatcup removal between both treatments appeared to be the main factor affecting the lack of differences on MD, in agreement with data reported by Upton et al (2019) and Silva Boloña et al (2019). The 50% milk flowrate switch-point is the maximum that can be set by the user in this AMS, and it is possible that a higher switch-point might produce a significant effect on MD.…”
Section: Short Communicationsupporting
confidence: 90%
“…Additionally, it was estimated that by increasing the milk flowrate switch-point on the quarter with the longest milking duration from 30 to 50% of the quarter's 30-s rolling average milk flowrate, MD of that quarter could be reduced by 30 s (Silva Boloña et al, 2020). However, in the study of Silva Boloña et al (2020), the differences on MD were at the quarter level, which may not necessarily result in a reduction in udder MD or box time (BT), as opposed to the udder level for the Upton et al (2019) and Silva Boloña et al (2019) trials.…”
Section: Short Communicationmentioning
confidence: 93%
See 1 more Smart Citation
“…In the experiment we observed higher milk flow for multiparous cows, which corresponds with the standard milk flows of Holstein cattle (Upton et al, 2019). The period in which the cows reached the highest lactation affected the AMF when early peaking cows had worse values for AMF.…”
Section: Discussionsupporting
confidence: 64%
“…In order to reduce the crawl of two-chamber teat cups on nipples of the mammary gland, the mass of the suspended part of the vacuum milking machine is usually changed [6,7,8].…”
Section: Introductionmentioning
confidence: 99%